Propylthiouracil-induced hypothyroidism protects ionizing radiation-induced multiple organ damage in rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; YEGEN, BERRAK; ATASOY, BESTE MELEK; ERZİK, CAN; ŞENER, GÖKSEL; KABASAKAL, LEVENT (BIOSCIENTIFICA LTD, 2006)
The objective of this study was to examine the potential radioprotective properties of propylthiouracil (PTU)-induced hypothyroidism against oxidative organ damage induced by irradiation. Sprague-Dawley rats were pre-treated with saline or PTU (10 mg/kg i.p.) for 15 days, and were then exposed to whole-body irradiation (800 cGy). A group of rats were decapitated at 6 h after exposure to irradiation, while another group was followed for 72 h after irradiation, during which saline or PTU injections were repeated once daily. Lung, liver, kidney and ileum samples were obtained for the determination of malondialdehyde (MDA; an index of lipid peroxidation) and glutathione (GSH, an antioxidant) levels, myeloperoxidase activity (MPO; an index of tissue neutrophil accumulation) and collagen contents, while oxidant-induced DNA fragmentation was evaluated in the ileal tissues. All tissues were also examined microscopically and assayed for the production of reactive oxidants using chemiluminescence (CL). Lactate dehydrogenase (LDH), an indicator of tissue damage, and turnout necrosis factor-alpha (TNF alpha) were assayed in serum samples. Irradiation caused a significant decrease in GSH level, which was accompanied by significant increases in MDA levels, MPO activity, CL levels and collagen content of the tissues studied (P < 0.05-0.001). Similarly, serum TNFa and LDH were elevated in the irradiated rats as compared with the control group. On the other hand, PTU treatment reversed all these biochemical indices, as well as histopathological alterations induced by irradiation. Our results suggested that PTU-induced hypothyroidism reduces oxidative damage in the lung, hepatic, renal and ileal tissues probably due to hypometabolism, which is associated with decreased production of reactive oxygen metabolites and enhancement of antioxidant mechanisms.
Keywords: INDUCED OXIDATIVE STRESS; LIPID-PEROXIDATION; LIVER-MITOCHONDRIA; ANTITHYROID DRUGS; REACTIVE OXYGEN; THYROID STATUS; INJURY; MYELOPEROXIDASE; HYPERTHYROIDISM; DYSFUNCTION